Isolated left side superior vena cava in a dialysis patient: Right direction, wrong turn!. Issue 3 (29th December 2021) - Bagai, Sahil; Khullar, Dinesh; Gandhi, Kunal; Panigrahi, Deepak; Bashir, Shahnawaz; Saxena, Vivek
Abstract: Tunneled catheter insertion is a routine procedure undertaken by nephrologists world over. However, the presence of a venous anomaly can always test one's skills and can give them anxious moments. Persistent left superior vena cava (SVC) is the most common venous anomaly. We share our experience of successfully placing a hemodialysis central venous catheter in a very rare congenital anomaly wherein patient had persistent left SVC with agenesis of the right SVC.